Efektivitas Fungi Mikoriza Arbuskula yang Diproduksi dengan Teknik Fortifikasi Nutrisi Berbeda terhadap Produktivitas Stylosanthes guianensis pada Cekaman Kekeringan: Effectiveness of Arbuscular Mycorrhizal Fungi Produced by Different Nutrient Fortification Techniques on the Productivity of Stylosanthes guianensis in Drought Stress - Marzukah; Manuhara Karti, Panca Dewi; Prihantoro, Iwan (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
This study aimed to test the effectiveness of arbuscular mycorrhizal fungi (AMF) products against stylo plants (Stylosanthes guianensis) under drought stress conditions. The research design used a factorial complete random pattern (CRD) with 2 factors. Factor A was AMF: F0 (control), FU (superior AMF as a comparison), FIPB1 (1000ppm ABmix nutrient fortification technique), FIPB2 (2000ppm ABmix nutrient fortification technique), FIPB3 (3000ppm ABmix nutrient fortification technique). Factor B was the drought level, 100% field capacity (FC), 60% FC (medium dry level), and 40% FC (high dry level). The fertilizer for control plants (without AMF) was 100% dose, while plants with AMF were given a 50% dose, adding AMF ± 20 grams. The results showed an interaction between the drought factor and the different types of AMF. AMF was effective in symbiosis with stylo plants at all levels of drought. FIPB1 and FIPB2 could increase plant adaptation up to 60% FC. All AMF inoculations effectively increased leaf chlorophyll content at all drought levels. Biomass accumulation in FU and FIPB1 plants produced the best biomass. The research concluded that the quality of AMF produced with different nutrient fortifications were as good as the superior AMF (FU). Inoculation of AMF products (IPB1, IPB2, and IPB3) with 50% fertilization effectively increased the adaptation and production of Stylosanthes guianensis to a drought level of 60% FC compared to control (without AMF, 100% fertilization). Key words: Arbuscular mycorrhizal fungi, drought level, productivity, Stylosanthes guianensis